Impacto de los factores institucionales del sistema electoral en la fragmentación partidaria. Un análisis de las elecciones para concejos municipales en el Valle del Cauca (1997-2011) (2015)
This paper analyzes, in aggregate form, the levels of fragmentation which existed in local council elections in the 42 districts of Valle del Cauca between 1997 and 2011; specifically, how a range of institutional variables contributed to this fragmentation, such as the size of the district and the reform of the electoral system in 2003. In the case of the latter, there is a particular focus on the limited impact that it had, generating significantly different results from those observed in other districts, such as the Senate (National), or the House of Representatives (Departments). This shows that many of the hasty generalizations - be these implied or explicit - that stem from the above analyses do not necessarily apply on a sub-national level, which should not be understood as being directly linked to what takes place at the national level.